Application of Mariapps at PT. Meratus Line Surabaya in The Crewing Management System - Suryadi, Awel; Romanda Annas Amrullah; Aprilianto, Rio (LPPM AKMI SUAKA BAHARI CIREBON, 2026)
This research examines the potential for digital adoption, as manual crewing management in Indonesian shipping creates inefficiencies, errors and compliance risks; however, scant research exists on this issue in Indonesia. It investigates how a leading shipping company in Indonesia is using this cloud-based crewing app to manage crew data, orchestrate paperless operations and improve ramp efficiency. Purpose – To examine Mariapps implementation outcomes within the crewing management system at PT. Meratus Line Surabaya. Methodology – Qualitative descriptive design; data collected via semi-structured interviews, observation, and documentation analysis from 15 purposively selected participants over two weeks in Surabaya. Findings – Mariapps reduced office visits by 91 percent, paper use by 87 percent, and eliminated certification compliance failures through centralised cloud-based crew data management. Originality – This study presents the first empirical investigation of Mariapps implementation within an Indonesian national shipping company, addressing a critical gap in maritime human resource management literature by providing evidence-based insights into digital crewing system adoption outcomes in a developing economy context.